Maternal obesity mediated predisposition to respiratory complications at birth and in later life: understanding the implications of the obesogenic intrauterine environment. (January 2017) - McGillick, Erin V.; Lock, Mitchell C.; Orgeig, Sandra; Morrison, Janna L.
Summary: More women than not are entering pregnancy either overweight or obese. This presents a significant health care burden with respect to maternal morbidities and offspring complications at birth and in later life. In recent years it has also become clear that maternal obesity is an even greater global health problem than anticipated, because the effects are not limited to the mother but are also programmed in the fetus, known as the 'intergenerational cycle of obestiy'. Despite a large body of epidemiological evidence reporting outcomes of obese pregnancies, including offspring respiratory complications, much less is known about the molecular effects of maternal obesity on fetal lung development. This review focuses on the influence of altered substrate supply associated with the obesogenic intrauterine environment on fetal lung development. Understanding the molecular mechanisms contributing to altered fetal lung development will lead to improved respiratory outcomes for offspring at birth and in later life.